Mediastinal space-occupying lesion – Mature teratoma: A case report (Indian Journal of Case Reports, 2026)
Mediastinal teratomas are germ cell tumors located in the anterior mediastinum, representing the most common extra-gonadal germ cell tumors. They account for approximately 15% of anterior mediastinal masses in adults and approximately 25% of anterior mediastinal masses in children. Here, we report a case of successful surgical management of a large mediastinal mature teratoma in a 6-year-old boy. This case highlights an uncommon cause of chest pain in children and underscores the importance of considering mass lesions in the differential diagnosis